2017
DOI: 10.1016/j.je.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between nutrition knowledge and dietary intake among primary school children in Japan: Combined effect of children's and their guardians' knowledge

Abstract: BackgroundImproving the dietary habits of children is important to decrease the future burden of noncommunicable diseases. While various food education programs have been implemented worldwide, evaluation of nutrition knowledge is difficult, even at baseline. Further, the relationship between nutrition knowledge and dietary intake has not been clarified in non-western countries.MethodsAfter developing nutrition knowledge questionnaires for Japanese primary school children and adults, we examined whether higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 49 publications
6
99
1
8
Order By: Relevance
“…This study focused on data of adult individuals from the latest round of the survey. Inclusion criteria were: (1) adults aged 18 years and over; (2) adults who can answer the questions independently. Exclusion criteria were: (1) households with missing data on health consumption and overall consumption expenditure;…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This study focused on data of adult individuals from the latest round of the survey. Inclusion criteria were: (1) adults aged 18 years and over; (2) adults who can answer the questions independently. Exclusion criteria were: (1) households with missing data on health consumption and overall consumption expenditure;…”
Section: Datamentioning
confidence: 99%
“…Previous evidence has shown that an unhealthy diet was admittedly one of the critical contributors to obesity. Previous systematic reviews which focused on the relationship between the nutrition knowledge and dietary intake showed that, as an integral component of health literacy, low nutrition knowledge has a significant association with the poor eating habits and bad health conditions [2]. Health literacy includes the level of knowledge, personal skills and confidence to take action to improve personal and community health by changing personal lifestyles and living conditions [3].…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional knowledge of female pupils was higher than male in the study of Naeeni et al [26], Tallarini et al [27] and Asakura et al [28].…”
Section: Discussionmentioning
confidence: 77%
“…Second, our targeted outcomes were limited to direct assessment of food preferences and child report of nutrition and health knowledge. Although both of these outcomes have been associated with consumption in previous research (1,11,12) , future research evaluating the curriculum would benefit from the inclusion of pre-and post-test assessments of fruit and vegetable consumption. Finally, although the short-term intervention was found to effective, we did not have a long-term follow-up to assess the extent to which the effects were maintained.…”
Section: Discussionmentioning
confidence: 97%